Diet Diversity in Andasibe, Madagascar. (29th May 2020) - Parker, Holly; Farris, Alisha; Miketinas, Derek
Abstract: Objectives: In Madagascar, over 75% of the population is impoverished and 50% of children experience stunted growth with lifelong health and developmental implications. Beyond inadequate energy intake, diet homogeneity contributes to macronutrient and micronutrient deficiencies underlying underdeveloped organ and skeletal system. Research measuring diet diversity of the rural Malagasy population is lacking. A pilot diet-diversity study was conducted in the rural village of Andasibe to identify specific dietary components missing from the Malagasy diet. Methods: Diet diversity data were obtained using guidelines established by the Food and Agriculture Organization of the United Nations. Over a 6-week period, 24-hour dietary recalls were collected of 150 representative adult household members- typically the mother or father of the household. Subjects provided verbal accounts of food and beverages consumed the day prior. Researchers then guided participants through a list of foods to capture any forgotten items. Foods recorded in the dietary recalls were assigned to categories based on nutrients of interest related to malnutrition and other diseases of nutrition inadequacy. Diet diversity scores (DDS) were assigned corresponding to food categories included in the 24-hour recall. Results: The average DDS of all surveys was 4 of a possible 9, corresponding to "medium" diet diversity. 37% of subjects received a "low" DDS and consumed between 1–3 food categories per day. 15% of participants received a "high" DDS and consumed between 6–8 categories per day. Categories unreported in the average recall were "legumes, nuts, and seeds"; "vitamin A-rich fruit and vegetable"; and "milk and milk products". Animal protein from sources such as meat or fish, dairy products, or eggs was not reported in most recalls. Conclusions: Low consumption of protein, vitamin A, and iron-containing items on a given day may be indicative of dietary inadequacies related to stunting and morbidity. Diet diversity data allows for basic quantification of the extent of dietary homogeneity in Andasibe, which likely mimics that of other Malagasy villages and identifies priority areas for future nutrition intervention. Funding Sources: Funding was provided by Auburn University's Office of Undergraduate Research and the College of Human Sciences.